2021
DOI: 10.1002/ejic.202100106
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium Encapsulated within Silicalite‐1 Zeolite as Highly Efficient Catalyst for Nitrous Oxide Decomposition: From Single Atoms to Nanoclusters and Nanoparticles

Abstract: The size of metal species plays a pivotal role in governing catalytic performance of supported metal catalysts. In this work, a series of Rh encapsulated within silicalite-1 catalysts with different sizes were prepared by one-pot hydrothermal method and employed to catalyze the decomposition of N 2 O. Detailed structure determinations by HAADF-STEM, XPS and CO-DRIFTS demonstrate that subtle modulation of the encapsulated Rh species were achieved easily from single-atom to nanoclusters and nanoparticles by cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Pd@ZSM-5-SGP (Figure d, e) and Pd@SSZ-13-SGP (Figure g, h) are irregular spheres with dimensions of 200–500 nm; Pd@NaA-SGP (Figure j, k) and Pd@Beta-SGP (Figure m, n) have irregular crystals with dimensions of 30–100 nm. The ultrasmall diameters (∼ 2.0 nm) and narrow size distributions of Pd nanoparticles in these zeolites suggest that this synthesis strategy has the same confinement effect as the traditional hydrothermal method, in which zeolite matrices effectively inhibit the accumulation of metal nanoparticles. , …”
Section: Resultsmentioning
confidence: 99%
“…Pd@ZSM-5-SGP (Figure d, e) and Pd@SSZ-13-SGP (Figure g, h) are irregular spheres with dimensions of 200–500 nm; Pd@NaA-SGP (Figure j, k) and Pd@Beta-SGP (Figure m, n) have irregular crystals with dimensions of 30–100 nm. The ultrasmall diameters (∼ 2.0 nm) and narrow size distributions of Pd nanoparticles in these zeolites suggest that this synthesis strategy has the same confinement effect as the traditional hydrothermal method, in which zeolite matrices effectively inhibit the accumulation of metal nanoparticles. , …”
Section: Resultsmentioning
confidence: 99%
“…C s -corrected STEM and EXAFS analyses revealed that single Rh atoms were confined within sinusoidal 5-MRs and stabilized by framework oxygen atoms of the zeolite (Figure c–e). Considering the significance of industrial propane dehydrogenation (PDH) process that can greatly meet the increasing global demand for propylene, ammonia, and EDA ligands stabilization method were also applied to the widely used Pt-based catalyst system toward solving their fast deactivation, severe sintering, and poor propylene selectivity problems. For instance, Corma and co-workers successfully synthesized K-PtSn@ MFI catalysts via one-pot synthesis containing metal–ethylenediamine complexes in the synthesis gel . A combination of high-resolution HAADF-STEM and integrated differential phase-contrast (iDPC) imaging techniques indicated that most subnanometric bimetallic PtSn clusters were preferentially located in the sinusoidal channels of purely siliceous MFI -type zeolite, whereas a very small amount of clusters were found in the straight channels or at the intersectional voids.…”
Section: Synthetic Strategiesmentioning
confidence: 99%
“…Notably, the single-atom catalysts can reduce the cost of catalysis via maximizing the efficiency of atom utilization, offering more active sites via adjusting the geometry and electronic configuration. 32,69 Zhang et al 70 encapsulated Au in amino-modified silica spheres, which showed excellent catalytic behavior and durability in high temperature carbon monoxide oxidation. Furthermore, the size of AuNPs was reduced from 2.3 nm to 1.5 nm by varying the number of metal precursors and showed high catalytic performance in catalytic oxidation reactions, reflecting the inherent size effect of Au nanoparticles on inert carriers.…”
Section: Confined Synthesis Strategiesmentioning
confidence: 99%